The Existence of Macapat Songs in the Era of Modernization: A Study of Shifting Functions and Revitalization Strategies - Perwita, Risma; Werdiningsih, Yuli Kurniati; Alfiah, Alfiah (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2024)
Tembang macapat, as a literary and cultural heritage of Javanese civilization, faces serious threats due to cultural value shifts in the modernization era. This study aims to analyze the existence of tembang macapat among the younger generation, identify factors causing its functional shift, and formulate revitalization strategies. The study employs a descriptive-qualitative approach with digital ethnography and content analysis methods. Data were collected through in-depth interviews with 15 informants (macapat artists, educators, and young people), participatory observation in arts communities, and tembang text documentation. Analysis was conducted using source and method triangulation. The results reveal three key findings: (1) the existence of tembang macapat among young people (aged 13-25) has declined significantly, with only 12% of respondents able to perform the tembang correctly; (2) the functional shift of tembang macapat from a moral education medium to a passive cultural artifact is triggered by digital culture dominance, weakening intergenerational transmission, and absence of relevant curriculum; (3) effective revitalization requires the integration of digital platforms, local community engagement, and local wisdom-based curriculum reform. This research contributes theoretically to ethnomusicology and cultural studies, as well as practically for education and cultural policy stakeholders.